ALUMINUM ALLOYS BY ECAP CONSOLIDATION FOR INDUSTRIAL APPLICATION - Agus Pramono; Anistasia Milandia; Kurnia Nugraha; Moch Fawaid (VANOS Journal of Mechanical Engineering Education, 2017)
Affecting factor of importance in industrial applications of Powder Metallurgy is a process of consolidation, the fabrication process with the good parameters by increasing of the bond strength on the surface to reduce the number of pores. In particular, methods of Severe Plastic Deformation (SPD) overcoming a number of difficulties associated with residual porosity in the sample which solidified. Ultrafine–Grained (UFG) materials processed by ECAP usually show unique mechanical properties such as; high yield stress at low strain hardening, good ductility on low temperatures and high strain-rate super-plasticity at high temperatures. Production of Al alloy growing rapidly, particularly in the automotive industry. Although high-strength aluminium alloys containing Mg and Si (6xxx series aluminium alloys) which are easily reached, for formability processes is not sufficient to be applied. Therefore, much research has focused on increasing the formability of these alloys through heat treatment. High strength aluminium alloy, such as alloy AA7XXX, which combines the power of high-density ratio with excellent mechanical properties, is widely used for aviation applications, superplastic forming into the high-volume fabrication of components in the automotive. Consumer products industry is currently limited because of the relatively low strain rate. AA6XXX are some of the alloys materials, mostly used currently covering the whole range of industry. Applications of AA6XXX easier to process than AA7XXX because of properties the material elasticity, AA7XXX tend to form internal cracks as a result of microsegregation. That way heat treatment is required to improve the properties of the material when it is processed by ECAP.